Size and position invariant visual representation supports retinotopic maps via selective backward paths A dynamic second order neural network model for a possible functional role of recurrent connections in the visual cortex. - Stoecker, Michael (Neurocomputing :an international journal.)
A dynamic multi-layered neural network performing scale and position invariant pattern recognition has been simulated. The model consists of a set of retinotopically organized layers that label objects via temporal signal correlations (synchronization coding). The successive set of layers computes scale and position invariance and functions as a dynamic associative memory in which objects can invariantly be stored and retrieved. Model neurons are arranged in six layers and coupled in forward direction via feeding connections and in lateral and backward directions via linking connections. Feeding connections manage the function of feature extraction and pattern recognition while linking connections support synchronizations among mutually coupled neurons. The most important property of the associative memory is its ability to support the retinotopic representation of a visual object via selective backward paths. For this, a special backward network has been included that is selectively activated by the forward pathway performing the invariance operation from the retinotopic layers to the associative memory. If a certain object in the input pattern is recognized by the associative memory, the synchronized signals of the object's memory neurons are routed back selectively to that position of the retinotopic network where the object is actually represented. Due to this backward coupling, the affiliation of neurons to assemblies can be re-defined by modifying the temporal synchronizations in the retinotopic layers. We demonstrate the effect of top-down influence on figure/ground separation and pattern recognition for different visual objects and scenes in computer simulations. It improves the segmentation of images containing multiple objects, including overlapping patterns of equal brightness, and it improves the rate of recognition. It is probable that our model can also be modified for other sensory modalities and it is proposed that selective feedback routing is one of the possible roles the numerous cortical backward projections may play.